Youth's Concepts on Quality of Life between Materialism and Environmentalism. An Empirical Study in the Context of (Education for) Sustainable Development - Oberrauch, Anna; Keller, Lars (Journal of Geography Education, 2017)
New curricula, educational standards, and competence models related to the subject of geography (and economics) emphasize the necessity to address the topic of quality of life in strong association with the basic principles of sustainable development. In the article at hand, we want to present results of a study investigating to what extent students are inspired to question established concepts of quality of life after having participated in a research-education-cooperation, focusing on quality of life and sustainability and implementing principles of moderate constructivism. In a cross-sectional study, 195 students aged 15-17 years were asked about their individual concepts of quality of life. 76 of these students from four classes in Northern (Austria) and Southern Tyrol (Italy) then participated in the research-education-cooperation. The changes in their concepts of quality of life were investigated in a pre-post-test comparison. The analysis of the students' concepts focuses on the significance of materialistic/financial aspects and of an intact natural environment for quality of life. The results show that the majority of the students are encouraged to reflect upon existing concepts in relation to both of these characteristics. Ideas for the practical implementation in geography (and economics) lessons contributing to Education for Sustainable Development are derived from these results.
Keywords: students' concepts, moderate constructivism, quality of life, (Education for) Sustainable Development